An Analysis of Using Mind Mapping Technique to Improve EFL Students’ Writing Ability - Nia Nidayanti; Usman Kasim; Hendra Heriansyah (Universitas Syiah Kuala, 2022)
This study investigates the effectiveness of using mind mapping technique to improve students’ writing ability. This study is a library research and used content analysis method to analyze the data. Of the 5 (five) journals and previous research about using mind mapping technique to teach English, all of them proved the technique to be effective. The findings showed that using mind mapping technique also improves students’ skill in writing aspects such as grammar, vocabulary, and idea organization. Furthermore, the biggest challenge in conducting mind-mapping technique was some of the students did not understand the characteristic of a mind mapping quite well. They wrote too much sentences in their mind maps. Thus, the solution applied by the previous researcher was using a warm up activity that is related to the mind-mapping technique to increase students’ motivation in writing and students’ understanding about the use of mind-mapping technique. Finally, the researcher suggests the English teachers to apply various learning activities and implement mind-mapping technique to motivate students such as using various media and pictures in teaching and learning of writing.